2021
DOI: 10.1097/aud.0000000000001122
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cases of Auditory Neuropathy Illuminate the Importance of Subcortical Neural Synchrony for Speech-in-noise Recognition and the Frequency-following Response

Abstract: Objectives: The role of subcortical synchrony in speech-in-noise (SIN) recognition and the frequency-following response (FFR) was examined in multiple listeners with auditory neuropathy. Although an absent FFR has been documented in one listener with idiopathic neuropathy who has severe difficulty recognizing SIN, several etiologies cause the neuropathy phenotype. Consequently, it is necessary to replicate absent FFRs and concomitant SIN difficulties in patients with multiple sources and clinical presentations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…Besides that, the findings of wave V delays have also been found in children with the presence of neurophysiological changes in individuals exposed to other neonatal infections, such as congenital toxoplasmosis, autism spectrum disorder, dyslexia, and auditory neuropathy 17,18,[30][31][32][33] . This deficit might be associated with behavioral difficulties agreeing with the findings of other researchers 16 who propose that prenatal exposure to the Zika virus may disrupt auditory development.…”
Section: Ffr and Gendermentioning
confidence: 88%
See 1 more Smart Citation
“…Besides that, the findings of wave V delays have also been found in children with the presence of neurophysiological changes in individuals exposed to other neonatal infections, such as congenital toxoplasmosis, autism spectrum disorder, dyslexia, and auditory neuropathy 17,18,[30][31][32][33] . This deficit might be associated with behavioral difficulties agreeing with the findings of other researchers 16 who propose that prenatal exposure to the Zika virus may disrupt auditory development.…”
Section: Ffr and Gendermentioning
confidence: 88%
“…The infants afflicted with toxoplasmosis exhibited elevated reactions in the latency measurements of waves V, A, E, F, and O waves, and diminished reactions in wave amplitude measurements A and F 17 . Another study showed that there seems to be damage in the FFR responses in individuals with auditory neuropathy, but only in the condition in which there is the presence of competitive noise 18 .…”
Section: Introductionmentioning
confidence: 99%